Light and dark trait subtypes of human personality – A multi-study person-centered approach. (1st October 2020) - Neumann, Craig S.; Kaufman, Scott Barry; ten Brinke, Leanne; Yaden, David Bryce; Hyde, Elizabeth; Tsykayama, Eli
Abstract: Is human nature good or evil? Light or dark? Machiavelli described human nature as selfish and greedy. Abraham Lincoln appealed to the better angels of our nature. Drawing on primate research and human personality science we provide insight into this centuries-old debate. Latent profile analyses of self-reports from two general population samples (Total N = 36, 788) uncovered distinct personality subtypes, a "dark" trait profile (Machiavellian, narcissistic, psychopathic traits), a "light" trait profile (Kantianism, humanism, faith in humanity), and a "middle" subtype threading between the other two. The light subtype evidenced affiliative interpersonal functioning and greater trust in others, as well as higher life satisfaction and positive self-image. The dark subtype reflected interpersonal dominance, competitiveness, and aggression. In both general population samples, the dark trait subtype was the least prevalent. However, in a third sample of U.S. Senators (N = 143), based on observational data, the dark subtype was most prevalent and associated with longer tenure in political office, though less legislative success. Results suggest that human nature reflects both light and dark features, serving affiliative (pro-social) and dominance (pro-self) functions, with subtype prevalence varying considerably based on profession.